2015
DOI: 10.3329/baj.v18i1.25562
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Intercropping Vegetables and Spices Relayed with Pointed Gourd

Abstract: An intercropping experiment was conducted at the Regional Agricultural Research Station, BARI, Ishurdi, Pabna during 2007-2008 and 2008-2009 to find out the suitable intercrop combination for increasing total productivity and returns. Seven treatments, viz. sole pointed gourd, two times lalshak + two rows turmeric in between pointed gourd lines, two times spinach + two rows turmeric in between pointed gourd lines, one time bushbean + two rows turmeric in between pointed gourd lines, two times lalshak + two ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
1
4
0
Order By: Relevance
“…The LER over 1 (unity) also indicated more land utilization capability for relay cropping than actual mono-cropping land [34,35]. The results are in agreement with the previous findings [32,36,37].…”
Section: Land Equivalent Ratio (Ler)supporting
confidence: 91%
“…The LER over 1 (unity) also indicated more land utilization capability for relay cropping than actual mono-cropping land [34,35]. The results are in agreement with the previous findings [32,36,37].…”
Section: Land Equivalent Ratio (Ler)supporting
confidence: 91%
“…Intercropping is a system that might be increase total production and profitability per unit area per time per inputs without affecting the production of the sole crops (Islam et al, 2013). Pointed gourd (Trichosanthes dioica) is an important vegetables crop of Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Sullivan (2003) mentioned that 1.25 LER value revealed that the obtained yield in the total intercrop would have required 25% more land if planted in pure stands. Also, Islam et al (2015) showed that LER of various crop combination ranged from 1.54 to 2.29 indicating 54-129% yield advantage by intercropping. High LER proportion might be attributed to the difference in time and place in ecological niche and consumption of nutrients and water.…”
Section: Discussionmentioning
confidence: 95%